ANALISIS IMPLEMENTASI KONSEP MERDEKA BELAJAR DALAM PEMBELAJARAN ISMUBA DI SMP MUHAMMADIYAH 9 TANGGULANGIN - Furoida, Fatin; Putra, Rahmad salahuddin Tri; Astutik, Anita Puji (Academy of Education Journal, 2023)
In this study there were several research objectives that were produced while the objectives were divided into three, including: 1). Urgency or explaining ismuba learning subjects implemented independent learning. study using the independent learning curriculum in ISMUBA lessons at SMP Muhammadiyah 9 Boarding School Tanggulangin. Background of the Problem Ismuba curriculum in junior high school as a benchmark for how the independent curriculum is applied. The formulation of the problem that is a problem at Muhammadiyah 9 Tanggulangin Middle school is the process of implementing ISMUBA (Islam/Al-Islam, Kemuhammadiyaan and Arabic) for Santriwan and Santriwati who carry out the process of adapting the independent curriculum with different methods and teaching in each personal Teacher. Formula problem Case study implementation of independent learning in ISMUBA learning at Muhammadiyah 9 Boarding School Middle School, there is a formulation of the problem as follows: 1). How is the subject of ismuba and learning independent learning. Method: Qualitative research believes in the influence of the situation on the thing being examined. A social researcher cannot understand human behavior without understanding the life framework of the situations in which people find themselves. They think, order and act in the context of their life framework. Research obtained from the results of interviews, observations, and documentation, then analyzed by reducing data, presenting data, and making conclusions.